Morpho-anatomical characters of the leaf and stem of Mandevilla coccinea (Hook. et Arn.) Woodson, Apocynaceae - Márcia do Rocio Duarte; Carina Rau Rivas Larrosa (Universidade de São Paulo, 2011)
Mandevilla coccinea (Hook. et Arn.) Woodson, Apocynaceae is a herb native to South America employed in folk medicine as an analgesic, anti-inflammatory and to inhibit snake venom effects. This work was carried out to study the morpho-anatomical characters of the leaf and stem in order to advance knowledge on this medicinal plant and on pharmacognostic quality control. The plant material was fixed and prepared according to light and scanning electron microtechniques. Its leaves are simple, alternate and ovate-obovate. The epidermis is uniseriate and coated with a thick and striate cuticle. The stomata are paracytic and occur on both foliar surfaces. The dorsiventral-like mesophyll has a sub-epidermal parenchymatic layer containing phenolic substances and is traversed by minor collateral vascular bundles. The midrib is biconvex and the petiole is concave-convex, both presenting bicollateral vascular bundles in an open arc. The stem is circular in transverse section and the epidermis remains in incipient secondary growth. A sub-epidermal parenchymatic layer containing phenolic substances, a discontinuous sclerenchymatic sheath of non-lignified fibres and cylinders of external phloem, xylem and internal phloem occur. Numerous branched laticifers and idioblasts with phenolic substances are present in the leaf and stem. Mandevilla coccinea (Hook. et Arn.) Woodson, Apocynaceae, é uma espécie herbácea nativa da América do Sul e empregada na medicina popular como analgésico, antiinflamatório e para inibir os efeitos de veneno de cobra. Este trabalho objetivou estudar os caracteres morfoanatômicos de folha e caule, a fim de fornecer conhecimento dessa espécie medicinal e para o controle de qualidade farmacognóstico. O material foi fixado e preparado de acordo com técnicas usuais de microscopia de luz e eletrônica de varredura. As folhas são simples, alternas e ovado-obovadas. A epiderme é unisseriada e recoberta por uma cutícula espessada e estriada. Os estômatos são paracíticos e ocorrem em ambas as superfícies foliares. O mesofilo tende a ser dorsiventral, apresenta uma camada subepidérmica parenquimática contendo compostos fenólicos e é percorrido por feixes vasculares colaterais de pequeno porte. A nervura central é biconvexa e o pecíolo é côncavo-convexo, ambos apresentando feixes vasculares bicolaterais em arco aberto no parênquima fundamental. O caule tem secção transversal circular e, em estrutura secundária incipiente, a epiderme permanece. Na sequência, encontram-se camada subepidérmica parenquimática contendo compostos fenólicos, bainha esclerenquimática descontínua composta de fibras não lignificadas, além de cilindros de floema externo, xilema e floema interno. Numerosos laticíferos ramificados e idioblastos com substâncias fenólicas estão presentes na folha e no caule.